The economics of the paramilitary war: an approximation to its financial sources (2005)
This article on the war economics of the paramilitary phenomena in Colombia, establishes a perspective of analysis on the interference of the phenomena in the economy of the nation as a whole, defining the possible actors and sectors directly or indirectly articulated to the financial process of the paramilitary presence in territorial contexts which overflow the counterinsurgency fight and inscribe themselves in their own dynamic of economical growth and regional development. The author starts from the explanations that the own paramilitary project makes of its financial sources to later on revise the information and argumentation being collected on this respect from different reflection and analysis fronts as a result of research processes carried out by state agencies and human rights institutions. Particular statements from contributors and victims of the paramilitary pressure on their economies have been taken into account, and their presentation has been made in a generic way.